Betrayal of trust : sex and power in professional relationships - Friedman, Joel, 1936-; Boumil, Marcia Mobilia (Westport, Conn. : Praeger, 1995)
In this thought-provoking book, women who have been coerced into sexual liaisons by lawyers, doctors, clergymen, educators, and other professionals reveal their experiences and the toll they took on their lives. Their recollections provide fresh insight into why some women are vulnerable to exploitation and what leads these men to risk their entire livelihoods to seduce their patient, client, or confidante.
What ensues is an in-depth examination of a type of relationship that begins with trust, feeds on real or imagined attraction, and often ends in emotional ruin.
In Betrayal of Trust, study of the actual relationship is only the beginning. Friedman and Boumil dig deeper to educate about exploitative situations. Readers will learn about early warning signs for recognizing when a professional relationship is crossing the dangerous boundary line between professionalism and sexual abuse.
On the legal front, new laws and statutes concerning sexual exploitation and malpractice are considered along with the time, financial, and emotional ramifications of lawsuits and other legal recourse. Victims are taken step-by-step through the long psychological healing process that leads from anger, shame, and guilt to vindication, resolution, and recovery. Related issues such as mutual consent and the ethics of a sexual relationship between a man and a woman after termination of their professional relationship are also discussed.
The book not only sheds light on the misuse of power in professional relationships, it also performs a valuable public service by pinpointing potential targets of abuse and offering hope for the thousands of victims who need to know why it happened to them and how they can pick up the pieces.
Ch. 1. Sexual Intimacy in Professional Relationships -- Ch. 2. Sexual Exploitation in the Mental Health Professions: The Paradigm -- Ch. 3. Sex and Power in Other Professional Relationships -- Ch. 4. Early Warning Signs: The Prelude to Exploitation -- Ch. 5. Filing a Complaint Against Your Therapist: The Mental Health Paradigm Revisited -- Ch. 6. Bringing Your Therapist to Court: The Costs and Benefits of Private Lawsuits -- Ch. 7. Legal Recourse for Sexual Exploitation by Other Professionals: The Emerging Law -- Ch. 8. Overcoming the Psychological Effects of Exploitation -- Ch. 9. Sex After Termination: The Nature of Consensual Relations, the Residue of Power, and the Unresolved Issues.
Includes bibliographical references and index.
Keywords: Sexual abuse victims -- United States; Sexually abused patients -- United States